TEACHING PASSIVE VOICE BY USING TASK-BASED LEARNING WITH INTEGRATED STEPS IN A PROCEDURAL FORM - FIRMANSYAH DIYATA (Ma'soem University, 2022)
Task-based learning is a teaching method that uses tasks to help students to understand the lesson materials. The students may gain the understanding by themselves or with the assistance of the handouts they explore or by the explanation given by the teacher. The task-based learning in this study is supported by a procedural form that assists the students as a reference when they are exploring the tasks. Through this procedural form, the students are hoped to acquire their understanding related of the process of changing active sentences into passive ones. Since the aim of the study is to find out the effectiveness of a teaching method, the approach that is conducted is the quantitative experimental method. This method of research is helped by document analysis, questionnaires, and interviews as its instrument. The study was held in a private university in Bandung and participated by 20 industrial engineering students with special requirements. The result of this study tells that the teaching method can help the students who participated to develop their understanding of the process of creating passive voices from their active ones by referring to the procedural form during their activity to solve the problems in the tasks.